Long term exposure to multiple environmental stressors induces mitochondrial dynamics imbalance in testis: Insights from metabolomics and transcriptomics - Shiqin Jiang; Tianli Nong; Ting Yu; Zhiyan Qin; Junyuan Huang; Zhaokun Yin; Shiqi Luo; Yating Lai; Jing Jin (Environment International)
Long-term exposure to adverse environment stressors (e.g. noise pollution, temperature, and crowding) impaired human health. However, research on the toxic effects of adverse environmental stressors on the male reproductive system is limited. This study employed integrated phenomics, metabolomics, and transcriptomics to investigate physiological disturbances in the testis of mice exposed to multiple adverse environmental stressors for two months. Phenotypic studies indicated that long-term environmental stimuli resulted in significant damage to the blood-testis barrier (BTB) and testes, evidenced by reduced testicular index, disrupted testicular tissue structure, abnormal tight junction protein expression, and spermatozoa abnormalities. Comprehensive multi-omics analysis revealed that long-term exposure to environmental stressors disrupted the BTB and testes, which was associated with mitochondrial metabolism disorders, including oxidative phosphorylation and fatty acid beta-oxidation, as well as glutathione and lipid metabolism alterations. Among these dysregulated pathways, significant alterations were observed in the critical regulators of mitochondrial fusion (MFN2) and fission (DRP1) within the BTB. Specifically, corticosterone treatment decreased tight junction protein expression, increased reactive oxygen species (ROS) levels, and impaired mitochondrial morphology and function, as evidenced by reduced mitochondrial membrane potential, elevated calcium ion concentration, and shortened mitochondrial length and network in vitro. Moreover, inhibiting DRP1 with Mdivi-1 or overexpressing MFN2 mitigated the corticosterone-induced reduction of tight junctions and mitochondrial dysregulation in TM4 cells. Collectively, maintaining mitochondrial homeostasis emerges as a promising strategy to alleviate the BTB and testicular injury induced by long-term exposure to multiple environmental stressors.